Periodicity of combined heat transfer from horizontal cylinders - Nayak, Shrinivas K., author; Sandborn, Virgil A., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1973)
Based on experimental and flow visualization studies, a model for directly opposed free and forced convection flow around a heated cylinder (0.01 mm diameter) was developed. Three modes of flow were identified. For velocities less than 15 cm/sec (cylinder Reynolds number, Redw=0.08) a free convection or a buoyant force dominated flow was observed. The interacting free convection plume and the ambient flow form a stagnation region well upstream of the heated cylinder. Heat was convected from the cylinder through the plume to the stagnation region. In the stagnation region random vortex pockets of heated mass were formed. For velocities greater than 15 cm/sec but less than 21.4 cm/sec the magnitudes of the forced and free convection flows were nearly equal. A periodic oscillation of the stagnation region was observed. The flow regime where the periodic oscillations occur was found to be defined by a specific relation between the Grashof and Reynolds numbers. The periodic oscillations, which were in the range from 3 to 15 cycles per minute, were correlated in terms of Strauhal number and Reynolds number. For velocities greater than 21.4 cm/sec the forced convection was found to dominate over the free convection. The stagnation region was fixed for each flow velocity at one position above the cylinder. A potential like flow (laminar sheet) was formed shrouding the thermal layer of the cylinder. The mean heat transfer from the cylinder decreases with increasing Reynolds number for both the case of dominant free convection and the case of equal free and forced convection. The mean heat transfer abruptly and rapidly increases with increasing Reynolds number in the forced convection dominated region. For all these cases the thermal layer surrounding the hot cylinder was approximately 600 times larger than the diameter of the cylinder.
CER72-73SKN-VAS23.
March 1973.
Prepared under Office of Naval Research Contract No. N00014-68-A-0493-0001, Project No. NR 062-414/6-6-68(Code 438), U. S. Department of Defense.
Circulating copy deaccessioned 2020.
Keywords: Heat -- Transmission; Fluid mechanics